A Calm Soul in Surah Al-Fajr 27-30 Al-Azhar Tafsir Perspective - Devi Nurqomariah; Yeti Dahliana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Humans consist of those whose daily lives demonstrate the unity of body and soul. Positive words and happiness go hand in hand when people interact. In this case, a person's condition for doing good deeds or actions that will result in heart disease is also influenced by their spirit. The heart is the estuary of joy and sorrow. A heart that feels satisfied and honest in worshiping solely to Allah SWT is said to have a healthy heart (qolbun salim). He can only be calm if he remembers Allah alone. The aim of this research is to study how to purify the soul according to Tafsir Al-Azhar and the meaning of the Muthmainnah lafadz in Surah Al-Fajr. Researchers use qualitative research methods, namely research that starts from the problems raised and the data to be collected, this research is qualitative research. Qualitative research is research of the type of library research (library research). Library research is research in which all data comes from written materials in the form of books, manuscripts, documents and other library data related to this research. One way to achieve inner peace is to entrust everything to God and consistently remember God. Positive outcomes of inner peace include the ability to make wise decisions, worry less, and live a life with balance. However, if the inner state is not calm, doubts and anxiety may arise and actions that are not wise will arise because they are influenced by desires.